Chemical Composition and Antimicrobial Activities of Essential Oil of Baisu, named Perilla frutescens (L.) Britt. - Hu, L.F.; Wang, X.J.; Zhu, H.X. (Asian Journal of Chemistry, 2014)
The essential oil was isolated by hydro-distillation from the Perilla frutescens (L.) Britt. The content and composition were analyzed by GC-MS. Thirty two different components were identified constituting approximately > 99 %. The major components were 1-(2-furyl)-1-hexanone (25.79 %), amylphenol (20.24 %), apiol (10.13 %) and o-xylene (9.33 %) etc. Among which, the apiol was detected from essential oil of Perilla frutescens leaves for the first time. The antifungal activity of the essential oil was tested by poisoned food technique against seven plant pathogenic fungi viz Verticillium dahliae, Gibberella zeae, Glomerella cingulata, Thanatephorus cucumeris, Botrytis cinerea, Phytophthora capsici and Pyricularia oryzae. The antibacterial activity of essential oil was tested by Oxford cup method against four bacteria viz Staphyloccocus aureus, Salmonella typhimurium, Bacillus subtilis and Bacillus anthracis. In general, the inhibiting ability of Perilla frutescens essential oil on plant pathogenic fungi was better than that on bacteria. Under the test concentration of 0.25 mg/mL, the inhibition rates of essential oil were above 50 % against all the seven fungi.